Food market integration in the West African Economic and Monetary Union (WAEMU): a dynamic panel approach - Laurent Oloukoi (Cogent Economics & Finance, 2024)
Our study examines the integration of food markets in West African Economic and Monetary Union (WAEMU) and assesses the role of bilateral trade. In this study, we hypothesize that each country has a market. We adopted the framework borrowed from Ravallion using a dynamic panel model. The theoretical approach used is the law of one price. The main conclusion is that food markets are segmented in the short term and there is a possibility that they will be integrated in the long term. Furthermore, even if trade development tends to reduce the gap in food prices between countries, this reduction is not significant. In this study, we ask a fundamental question: is there a co-movement of food prices in the West African Economic and Monetary Union (UEMOA)? The appropriate theoretical framework to answer such a question is the law of one price. We therefore analyze the integration of food markets in West Africa by highlighting the role that bilateral trade can play. The importance of our study lies on three levels. First, we draw the attention of state and non-state actors to the need to put in place policies to facilitate better integration of food markets in the short term. This could include improving transport and communications infrastructure, and reducing non-tariff barriers. Second, by showing that long-term integration possibilities exist, we encourage the pursuit of cooperation and food market development strategies. Third, we reveal that the bilateral trade necessary to equalize food prices between countries is not yet achieved in the WAEMU.
Keywords: E64; F10; F15; Q18; 330; Trade; food marketintegration; law of oneprice; dynamic panel; WAEMU